The effects of enhanced external counter-pulsation on post-acute sequelae of COVID-19: A narrative review - Huang Jiecheng; Fan Yuxuan; Wang Yongshun; Liu Jingjin (Open Medicine)
Some of the millions of patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have developed new sequelae after recovering from the initial disease, termed post-acute sequelae of coronavirus disease 2019 (PASC). One symptom is anxiety, which is likely due to three etiologies: brain structural changes, neuroendocrine disruption, and neurotransmitter alterations. This review provides an overview of the current literature on the pathophysiological pathways linking coronavirus disease 2019 to anxiety, as well as the possible mechanisms of action in which an increasingly scrutinized treatment method, enhanced external counter-pulsation (EECP), is able to alleviate anxiety. SARS-CoV-2 triggers increased inflammatory cytokine production, as well as oxidative stress; these processes contribute to the aforementioned three etiologies. The potential treatment approach of EECP, involving sequenced inflation and deflation of specifically-placed airbags, has become of increasing interest, as it has been found to alleviate PASC-associated anxiety by improving patient cardiovascular function. These functional improvements were achieved by EECP stimulating anti-inflammatory and pro-angiogenic processes, as well as improving endothelial cell function and coronary blood flow, partially via counteracting against the negative effects of SARS-CoV-2 infection on the renin–angiotensin–aldosterone system. Therefore, EECP could promote both psychosomatic and cardiac rehabilitation. Further research, though, is still needed to fully determine its benefits and mechanism of action.